Firm, Industry and Country Level Determinants of Capital Structure: Evidence from Jordan - El Bahsh, Rana; Alattar, Ali; Yusuf, Aziz N. (International Journal of Economics and Financial Issues, 2018)
This paper investigates the effect of firm and country factors on firms' leverage within the context of the Pecking Order and Trade Off theories. We use the fixed effects model over 15 years on firms listed in the Amman Stock Exchange in Jordan to determine the factors that influence short- term, long-term, and total liabilities. Results reveal that Jordanian firms prefer short to long- term debt. Size, growth, and risk affect firm trading- off between debt benefits and costs. Bank concentration and financial freedom have effect on firm's leverage. Corruption, inflation, and financial market development created opportunity to firms to increase and benefit from leverage. The internal nature of firms seems to reduce agency problems and refinancing risk which provides better access to external debt. This is the first study that explains the financial behavior of firms within macroeconomic variables through extended period, and distinguishes between industrial and services sectors. Keywords: Trade-off theory, Pecking order theory, Capital structure, Panel data analysis, country specific factors JEL Classifications: M410, M480